1999
DOI: 10.1034/j.1399-6576.1999.430413.x
|View full text |Cite
|
Sign up to set email alerts
|

Luxury lung perfusion in end‐stage liver disease during liver transplantation

Abstract: The low vascular resistance is accompanied by a high cardiac output. In spite of the high shunt fraction, these patients were not hypoxaemic. This is explained by the fact that the increased cardiac output leads to a decrease in arterio-mixed venous oxygen content difference and an increase in mixed venous oxygenation level, SvO2 86-88%, normal value approximately 70%. The VAeff/COeff in this study was approximately 0.5, i.e. the effective cardiac output, COeff is 235, 180 and 197% of the effective alveolar ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Other authors have also reported the elevation of MPAP after reperfusion during OLT in humans with end-stage liver disease [17][18][19]. At reperfusion, the expansion in preload and cardiac output without a similar afterload decrease is responsible for the steady increase in pressure [19].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Other authors have also reported the elevation of MPAP after reperfusion during OLT in humans with end-stage liver disease [17][18][19]. At reperfusion, the expansion in preload and cardiac output without a similar afterload decrease is responsible for the steady increase in pressure [19].…”
Section: Discussionmentioning
confidence: 90%
“…Mean pulmonary arterial pressure is frequently increased during the early postoperative period, in patients without previously observed pulmonary hypertension [18]. However, this preoperative increase of pulmonary pressure has not definitely been associated with later adverse outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The effective alveolar ventilation is defined as the ventilation in contact with the pulmonary circulation (26). Although the term "effective alveolar ventilation" is not currently used in respiratory physiology textbooks, Levy and Simmons (15), in 1974, introduced this term to characterize exclusively the ventilation of areas with maintained or increased perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless only in the last decade has the pathogenesis of hepatopulmonary syndrome (HPS) and its related clinical implications been discussed in depth (2)(3)(4)(5)(6)(7)(8). On the contrary, the paucity of publications in anesthesiological literature is evident and unexplainable (9)(10)(11)(12)(13). Yet, with the increasing prevalence of liver disease in the population and improved survival of these patients, a growing number of hepatopathic patients will undergo surgery (14,15) and consequently will require not only a surgeon's but also an anesthestist's attention.…”
mentioning
confidence: 99%